2018
DOI: 10.1037/dev0000544
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of likability, perceived popularity, and admiration in the early adolescent peer system in the United States and China.

Abstract: High social status youth are often influential in the peer system. Thus, they may serve as agents of cultural socialization if they exhibit characteristics that reflect cultural values (e.g., interdependence). This research examined the behavior that contributes to high social status in the United States and China. At each of 3 waves, 934 early adolescents (M = 12.7 years at Wave 1) made behavioral (i.e., prosocial behavior and academic engagement) and social status (i.e., likability, perceived popularity, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
45
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(52 citation statements)
references
References 69 publications
7
45
0
Order By: Relevance
“…A comparative study indicated that academic engagement not only was more strongly associated with social status in China (vs. the United States), but it was also a stronger predictor of youth's social status over time in China. This difference was most evident for perceived popularity (vs. likability and admiration) (Zhang et al, 2018).…”
Section: Academic Achievement Achievement Goal and Perceived Populamentioning
confidence: 96%
“…A comparative study indicated that academic engagement not only was more strongly associated with social status in China (vs. the United States), but it was also a stronger predictor of youth's social status over time in China. This difference was most evident for perceived popularity (vs. likability and admiration) (Zhang et al, 2018).…”
Section: Academic Achievement Achievement Goal and Perceived Populamentioning
confidence: 96%
“…Popularity can have both negative and positive consequences for adolescent development. Popular students are more likely to show low academic performance (Zhang et al 2018) and to engage in risk behaviors compared to their agemates (e.g., Moody et al 2011). Also, popular students have been found to have better social skills, more self-confidence, and lower levels of depression (Meijs et al 2010;Sandstrom and Cillessen 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Cultural values and norms have been found to influence the profiles that define social status (e.g., Chen & French, ; Li, Xie, & Shi, ; Zhang et al, ). Chinese culture as well as education highly value children’s good interpersonal character and academic success (Hsu & Wu, ), which may be especially relevant to children being preferred by classmates or being a class leader.…”
Section: Introductionmentioning
confidence: 99%
“…Individuals’ personal characteristics are proximal correlates of their social status (Asher & McDonald, ; Rubin et al, ). Numerous studies concerned with the correlates of children’s social status have focused primarily on children’s personal characteristics (e.g., Cillessen & Mayeux, ; Dai, ; Niu et al, ; Parkhurst & Hopmeyer, ; Zeng & Liu, ; Zhang et al, ). Cultural values and norms have been found to influence the profiles that define social status (e.g., Chen & French, ; Li et al, ; Zhang et al, ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation